The location choice of graduate entrepreneurs in the United Kingdom - Ely, Philip; Polonyová, E.; Ondoš, S. (2015)
The graduates’ startup formation process represents a possible future role for universities in the form of active-participation , when speaking of the regional development. Tracking the path of entrepreneurial graduates who are moving between home, university, and employment, allows us to identify the specific motives that determine their migration decisions. The choice of location of graduate entrepreneurs is naturally affected by the context of their home region, as the availability of resources leads to a rising entrepreneurial intention. Similarly, the location of the startups flourish in densely populated urban regions, as well as in wealthier locations. At the same time, the vibrancy of the local entrepreneurial ecosystems is enhanced through mutual exchange and collaboration; and the higher the number of startups already present in a region, the higher the probability becomes for interaction and creativity. A leading tendency, not least to be mentioned, is that the preference to start new businesses is connected to highly-skilled creative sectors of the economy.